Freshmen and Third Grade Students Perceptions on Their Soft Skills Acquirement in The Use of Collaborative Learning in English Classroom - Nia Nuryanti Permata (English Education Department, 2017)
It is said that soft skills are needed to have a successful life and career for students and can be trained in classroom by conducting collaborative learning. Then, polytechnic students have collaboration learning in their English classroom activity which is useful for their soft skills achivements. However, the students which have different level can have different perceptions on it. This research tries to compare students’ perceptions on their soft skills acquirement in the use of collaborative learning in English classroom in a state polytechnic. The first group is the freshmen, meanwhile the second group is the third grade students of Diploma 3. The study employs a qualitative research design, which is a case study. The data are gained from questionnaire, then observation and interviews are used to triangulate the data. The findings show that the freshmen perceive that they acquire soft skills in 90.9%, meanwhile the third graders are in 84.9%. This concludes that freshmen soft skills acquirement is higher than the third graders. It is recommended that collaborative learning method should be continued to develop the students’ soft skills, and the type of collaborative learning should be more appropriate for different grades of students.